All cause and disease specific mortality in patients with knee or hip osteoarthritis: population based cohort study. (8th March 2011) - Nüesch, Eveline; Dieppe, Paul; Reichenbach, Stephan; Williams, Susan; Iff, Samuel; Jüni, Peter
Abstract : Objective To examine all cause and disease specific mortality in patients with osteoarthritis of the knee or hip. Design Population based cohort study. Setting General practices in the southwest of England. Participants 1163 patients aged 35 years or over with symptoms and radiological confirmation of osteoarthritis of the knee or hip. Main outcome measures Age and sex standardised mortality ratios and multivariable hazard ratios of death after a median of 14 years' follow-up. Results Patients with osteoarthritis had excess all cause mortality compared with the general population (standardised mortality ratio 1.55, 95% confidence interval 1.41 to 1.70). Excess mortality was observed for all disease specific causes of death but was particularly pronounced for cardiovascular (standardised mortality ratio 1.71, 1.49 to 1.98) and dementia associated mortality (1.99, 1.22 to 3.25). Mortality increased with increasing age (P for trend <0.001), male sex (adjusted hazard ratio 1.59, 1.30 to 1.96), self reported history of diabetes (1.95, 1.31 to 2.90), cancer (2.28, 1.50 to 3.47), cardiovascular disease (1.38, 1.12 to 1.71), and walking disability (1.48, 1.17 to 1.86). However, little evidence existed for increased mortality associated with previous joint replacement, obesity, depression, chronic inflammatory disease, eye disease, or presence of pain at baseline. The more severe the walking disability, the higher was the risk of death (P for trend <0.001). Conclusion Patients with osteoarthritis are at higher risk of death compared with the general population. History of diabetes, cancer, or cardiovascular disease and the presence of walking disability are major risk factors. Management of patients with osteoarthritis and walking disability should focus on effective treatment of cardiovascular risk factors and comorbidities, as well as on increasing physical activity.